THERMAL STRAIN AND EXPANSION COEFFICIENT OF PbSb ALLOY UNDER STATIC AND DYNAMIC LOADING - Rammo, N N; Abd Al- Razak, A H (Al-Nahrain Journal of Science, 2010)
Thermal mechanical behavior of PbSb alloy subjected to static and dynamic loading inthe temperature range 30-200 oC and different loading schemes has been investigated. Thetake up strain is Hookian up to 100 oC and transfer to creep behavior for higher temperatures(